2002
DOI: 10.1038/sj.bmt.1703389
|View full text |Cite
|
Sign up to set email alerts
|

Second hematopoietic stem cell transplantation for the treatment of graft failure, graft rejection or relapse after allogeneic transplantation

Abstract: Summary:Failure to engraft after hematopoietic stem cell transplantation (graft dysfunction) or to sustain engraftment (graft rejection) is a formidable complication due to many possible factors. These include inadequate stem cell numbers, infections, graft-versus-host disease and immunological mediated processes. Fortunately, this complication is uncommon and can be overcome by additional hematopoietic stem cell infusions. Multiple treatment alternatives have been explored including hematopoietic growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 78 publications
2
115
0
9
Order By: Relevance
“…There are reports showing that some cases can achieve engraftment without any preconditioning regimen; 26,27 however, it is generally accepted that most pGF cases require some preconditioning treatment. 14 We consider that myeloablative conditioning is not required for the salvage HSCT in pGF patients because their marrow is already hypocellular; however, reduced-intensity conditioning may help engraftment. Our study showed that FLU and alkylating agents provide better engraftment probability without increasing NRM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports showing that some cases can achieve engraftment without any preconditioning regimen; 26,27 however, it is generally accepted that most pGF cases require some preconditioning treatment. 14 We consider that myeloablative conditioning is not required for the salvage HSCT in pGF patients because their marrow is already hypocellular; however, reduced-intensity conditioning may help engraftment. Our study showed that FLU and alkylating agents provide better engraftment probability without increasing NRM.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of graft failure is assumed to range from 2 to 20%, and the frequency depends on various factors such as stem cell source 1,2 and preconditioning regimen, [3][4][5] underlying disease, 5 HLA disparity 2,6,7 and the presence of anti-HLA Abs. 8 Salvage HSCT can rescue pGF patients, [9][10][11][12][13][14] and recent studies on adult pGF patients have showed the feasibility of using reduced-intensity conditioning containing fludarabine (FLU) and low-dose irradiation, 13,[15][16][17] including short-term preconditioning regimen 10,18 and an advantage of PBSC as the stem cell source for salvage HSCT. 19,20 However, the management of pGF patients is usually difficult because of their poor clinical status.…”
Section: Introductionmentioning
confidence: 99%
“…24 Several factors may be involved in this severe complication, such as compromised host marrow microenvironment, 25 infections with herpes viruses, 26 inadequate stem cell numbers 27 or, on the other hand, persistent host immunity, mediated by residual T and NK cells and HLA disparity. 28 It has been shown that CD3 þ /CD8 þ T cells of recipient origin frequently emerge in graft rejection.…”
Section: Engraftment and Gvhdmentioning
confidence: 99%
“…7 GF can be affected by many factors such as disease, prior therapy, conditioning regimen, T-cell dose, CD34 cell dose and T-cell depletion technique. 3,[19][20][21][22][23] A matched comparison between the present study and our prior study using CD3-depleted grafts is difficult because stem cell dose, proportion of patients with NM and proportion receiving low-dose TBI are somewhat different between the two studies. Recent studies reported that a GF rate after αβ-depleted HHCT for pediatric patients ranged from 12 to 16.2%.…”
Section: Discussionmentioning
confidence: 79%